+0  
 
0
436
1
avatar

√-1-5√-4

Guest May 16, 2015

Best Answer 

 #1
avatar+87334 
+5

√-1 - 5√-4  =

 

i  - 5√[-1 * 4] =

 

i - 5i√4  =

 

i - 5i(2)  =

 

i - 10i

 

-9i

 

CPhill  May 16, 2015
 #1
avatar+87334 
+5
Best Answer

√-1 - 5√-4  =

 

i  - 5√[-1 * 4] =

 

i - 5i√4  =

 

i - 5i(2)  =

 

i - 10i

 

-9i

 

CPhill  May 16, 2015

6 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.